Formation of pedogeochemical anomalies in zones impacts of industrial enterprises - Golovatyi, Sergey E.; Savchenko, Svetlana V.; Samusik, Elena A. (Journal of the Belarusian State University. Ecology, 2019)
On industrial sites and in the zones of influence of industrial enterprises, stable pedogeochemical anomalies are formed, the composition and contrast of which depend on the nature of production processes. On the territory of the machine-building industry, the pedogeochemical anomaly is represented by copper and zinc, to a lesser extent by nickel, chromium and lead. In the soils of the cement plant, the anomaly consists of zinc, lead and cadmium. At the enterprise specializing in cast iron and steel casting, the composition of the pedogeochemical anomaly includes copper, zinc, chromium, and also lead, nickel and arsenic. Within these anomalies, there are limited areas of halo contamination of soil with a higher content and a wider association of pollutant elements.
Keywords: pedogeochemical anomaly; pollutants; gross content of heavy metals; industrial enterprise; association of pollutant elements